2022
DOI: 10.3390/jpm12030477
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Rare Disease Patient Attitudes and Beliefs regarding Genetic Testing: Implications for Person-Centered Care

Abstract: Most rare diseases are genetic in etiology and characterized by a ‘diagnostic odyssey’. Genomic advances have helped speed up the diagnosis for many rare disorders, opening new avenues for precision therapies. Little is known about patient attitudes, experiences, and beliefs about genetic testing for the rare disease congenital hypogonadotropic hypogonadism (CHH). Methods: We conducted six focus groups with patients with CHH (n = 58). Transcripts were coded by independent investigators and validated by externa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…The cost associated with genetic testing emerged as a notable barrier for some study participants. This concern aligns with the findings from a qualitative study conducted in Boston, USA, where individuals affected by rare diseases identified the cost as the primary barrier preventing them from receiving genetic testing, with specific concerns around insurance coverage (Dwyer et al 2022 ). Similarly in an Australian discrete choice experiment study, participants reported a reluctance to genetic testing when presented with higher costs and requirement to disclose results to health insurers (Goranitis et al 2020 ).…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…The cost associated with genetic testing emerged as a notable barrier for some study participants. This concern aligns with the findings from a qualitative study conducted in Boston, USA, where individuals affected by rare diseases identified the cost as the primary barrier preventing them from receiving genetic testing, with specific concerns around insurance coverage (Dwyer et al 2022 ). Similarly in an Australian discrete choice experiment study, participants reported a reluctance to genetic testing when presented with higher costs and requirement to disclose results to health insurers (Goranitis et al 2020 ).…”
Section: Discussionsupporting
confidence: 73%
“…A participant in the current study conveyed a desire to undergo genetic testing and participate in research to contribute to advancing knowledge that could alleviate the burden of the condition for future generations. This motivation is consistent for other rare disease patients, whereby altruism is a strong catalyst for pursuing genetic testing, particularly in the context of research (Dwyer et al 2022 ).…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Accordingly, in a “Patient Attitudes and Beliefs” survey, it was observed that patients with congenital hypogonadotropic hypogonadism (CHH) are driven by altruism to pursue genetic testing. However, there is a substantial unmet need for genetic counseling to support pretest decision making and post-test counseling ( Dwyer et al, 2022 ). Furthermore, a survey evaluating the opinion of the members of RD social media groups on engaging with genetic counselors through social media found that PLWRDs and their family members were interested in connecting with genetic counselors through these platforms ( Yabumoto et al, 2022 ).…”
Section: Barriers To Rare Disease Diagnosismentioning
confidence: 99%
“…RDs are often characterized as “diagnostic odyssey,” with the average time to arrive at a correct RD diagnosis after presentation being 5 years. The diagnostic delays can impede treatment initiation and causes substantial psychological, emotional, and financial distress for patients and their caregivers ( Dwyer et al, 2022 ). Clinical genetic testing helps identify DNA anomalies that cause rare genetic disease.…”
Section: Introductionmentioning
confidence: 99%